2021
DOI: 10.3390/agriculture11080781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Low Protein Diets on the Production Traits and the Nitrogen Composition of Excreta of Broiler Chickens

Abstract: The main goal of the current study was to investigate the effects of feeding low protein (LP) diets on the performance parameters and excreta composition of broiler chickens. In total, 288 male Ross 308 day-old chickens were divided into two dietary treatment groups using six replicate pens with 24 chickens each. No LP diet was fed in the starter phase. The protein reduction in the grower and finisher phases were 1.8% and 2% respectively. Beside the measurements of production traits, on day 24 and 40 represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The uric acid concentration of excreta in broilers fed the control C diet was already quite low (12.54 mg/g dry matter), and maybe a further decrease was not possible by feeding LP diets. In our previous two experiments, the LP diets reduced the uric acid levels in the excreta when higher uric acid levels than in the present trial were measured in the excreta of broilers fed normal CP diets (17.65 and 15.30 mg/g dry matter) ( 31 , 43 ).…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…The uric acid concentration of excreta in broilers fed the control C diet was already quite low (12.54 mg/g dry matter), and maybe a further decrease was not possible by feeding LP diets. In our previous two experiments, the LP diets reduced the uric acid levels in the excreta when higher uric acid levels than in the present trial were measured in the excreta of broilers fed normal CP diets (17.65 and 15.30 mg/g dry matter) ( 31 , 43 ).…”
Section: Discussionmentioning
confidence: 41%
“…A common starter diet was fed because an early CP reduction would have had minimal impact on the total CP and soybean meal reduction, nitrogen emission, and final performance. In most trials, the reduction in dietary CP by 2% could be achieved without impaired production traits when at least three-phase feeding was used, pelleted diets were fed, and the diets were balanced in at least six limiting AAs ( 15 , 30 , 31 ). In our study, all performance traits of broilers fed LP diets met or exceeded the performance parameters of control birds fed the C diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the properties, benefits, and effects of probiotics differ and are specific to each strain. The single-strain probiotic C. butyricum reportedly failed to influence the cecal microflora composition of Ross 308 broilers, whereas Bacteroides , Oscillospira, and Faecalibacterium were the dominant genera in the C. butyricum -treated group ( Such et al , 2019 ).…”
Section: Butyricum Interacts With Gut Microbes Toregulate Intestinal ...mentioning
confidence: 99%
“…Feeding poultry with low-protein diets is an option, but their effects on the performance parameters and excreta composition of broiler chickens need to be investigated. It was found that the urinary N content of broiler chicken's excreta is lower than can be found in the literature, which should be considered in the ammonia inventory calculations [3]. The amount of phosphorus in the diet is also under debate.…”
mentioning
confidence: 95%